2023
DOI: 10.9734/jammr/2023/v35i105017
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of HPV-Related Cancers among University Students: A Cross-sectional Study

Abstract: Background: HPV is associated with some malignant neoplasms, especially cancers of the cervix, oropharynx, penis, anus and vulva. Aims: The aim of this study was to analyze the awareness of Human Papillomavirus-associated cancers among university students. Methodology: We conducted a cross-sectional research among medical students and student nurses from four institutions from June to December 2020. A questionnaire was utilized to obtain information about sexual behavior and awareness of HPV among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The pooled analysis of all included studies indicated that among university students, the knowledge level about this relationship ranged from 17.00% to 83.00%, with an overall pooled prevalence of 45.00% (95% CI: 35.00-55.00). This result is similar to the findings by Alzabibi et [11,23,25,30,12]. This suggests that while there is some awareness of the link between HPV and oropharyngeal cancer among university students, there is also significant room for improvement in knowledge dissemination and education in this regard.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The pooled analysis of all included studies indicated that among university students, the knowledge level about this relationship ranged from 17.00% to 83.00%, with an overall pooled prevalence of 45.00% (95% CI: 35.00-55.00). This result is similar to the findings by Alzabibi et [11,23,25,30,12]. This suggests that while there is some awareness of the link between HPV and oropharyngeal cancer among university students, there is also significant room for improvement in knowledge dissemination and education in this regard.…”
Section: Discussionsupporting
confidence: 89%
“…22 studies with 11.362 participants were included in this systematic review. These studies were conducted in different countries [11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. As depicted in Table 1, a total of 21 cross-sectional studies and 1 Cohort study, were included.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%